Titanium-based porous material for gas diffusion layer and preparation method thereof
By preparing a microporous titanium layer gas diffusion layer with a gradient pore structure on a titanium felt substrate, the disadvantages of existing materials in pore size and distribution state are solved, and efficient hydrogen energy conversion and utilization are achieved.
Patent Information
- Application Number
- CN202411015065.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-07-26
AI Technical Summary
The existing gas diffusion layer materials have the disadvantages of singleness in pore size and distribution state, which cannot meet the precise control needs of liquid/gas/electronics/heat distribution, resulting in low electricity-hydrogen-electric conversion efficiency and increased costs.
The microporous titanium layer structure attached to the titanium felt substrate is used to prepare the first and second titanium layers by ultrasonic spraying technology to form a gas diffusion layer with a gradient pore structure.
The interface relationship between the catalytic layer and the gas diffusion layer is optimized, the contact resistance is reduced, the utilization rate of low-load catalyst is improved, the deformation of the proton exchange membrane is suppressed, and the efficient preparation and utilization of hydrogen energy is achieved.
Smart Images

Figure CN118926535B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen utilization, and in particular relates to a titanium-based porous material for a gas diffusion layer and a preparation method thereof. Background Art
[0002] On the hydrogen production side, producing green hydrogen through water electrolysis using renewable energy has become a new development trend. Among them, PEM water electrolysis hydrogen production technology has become the best choice for combination with renewable fluctuating energy due to its advantages of high current density and fast dynamic response speed.
[0003] On the hydrogen application side, the chemical energy of hydrogen is generally converted into electrical energy through fuel cells in the form of electrochemical reactions for application. Among them, PEM fuel cells have the advantages of low operating temperature, short start-up time, low noise, and high specific power, making them very suitable for automotive and portable applications.
[0004] The membrane electrode assembly (MEA) is the core component of the PEM electrolyzer and PEM fuel cell. The gas diffusion layer (GDL) is responsible for conducting heat and charge from the catalyst layer, promoting gas-liquid two-phase mass transfer, and providing mechanical support for the MEA. It has an important influence on mass, heat and charge transfer, and largely determines the performance of the electrolyzer or fuel cell.
[0005] The anode-side GDL of the PEM electrolyzer usually uses stable and corrosion-resistant titanium-based materials to adapt to high anode potentials and harsh acidic environments. The cathode-side GDL of the PEM fuel cell usually uses hydrophobic-treated carbon fiber felt or stable and corrosion-resistant titanium felt.
[0006] As disclosed in patent JP2022145670A, a porous metal gas diffusion layer, a solid polymer fuel cell having the porous metal gas diffusion layer, and a water electrolysis device are provided. The gas diffusion layer for the solid polymer fuel cell includes a porous metal gas diffusion layer, and the porous metal gas diffusion layer is a layer composed of a metal porous sheet. As a porous metal gas diffusion layer, a metal porous sheet made of metal Sn or Sn alloy, metal Ti or Ti alloy, or stainless steel and having a plurality of through holes. Preferably, the metal porous sheet has dendrites of metal Sn or Sn alloy in a plurality of through holes.
[0007] The pores and structure of the gas diffusion layer have a significant impact on the electrocatalytic performance. Larger pores promote gas removal, but reduce electron transfer efficiency and reduce moisture in the adjacent anode / cathode catalyst layers. Conversely, small pores hinder gas discharge and increase mass transfer resistance.
[0008] Therefore, there are studies on modifying the original titanium felt and carbon fiber felt materials. For example, the treatment of titanium felt includes sintering an ultra-thin titanium microporous layer (about 20 μm) and a high-proportion precious metal layer (Pt or Ir) on a titanium mesh. For example, patent CN117385383A provides a method for preparing a proton exchange membrane PEM electrolyte water electrolysis gas diffusion layer, and the steps are as follows: suspension preparation: titanium powder is mixed with Nafion solvent to form a suspension; titanium felt cleaning: the titanium felt substrate is placed in a solvent for cleaning and oiling; suspension spraying: the prepared suspension is sprayed on one side of the gas diffusion layer using a spray gun to form a dense microporous layer; an MPL suspension is prepared using titanium powder, including 5 μm titanium powder and Nafion solution, and ultrasonically mixed for 15 minutes; ethylene glycol is added and ultrasonically mixed for 1 hour to make an MPL suspension; the titanium felt is ultrasonically cleaned with acetone, methanol, and ethanol for 15 minutes in sequence, and finally rinsed with deionized water for 15 minutes, and air-dried at room temperature for 24 hours; the dried titanium felt gas diffusion layer is mounted on a silicon wafer and placed horizontally in a large fume hood.
[0009] However, the above surface treatment of titanium felt, titanium mesh or titanium foam still has the disadvantage of uniform fiber / foam pore morphology on its surface. Such pore size and distribution state still cannot meet the requirements of precise control of liquid / gas / electron / heat distribution in the gas diffusion layer.
[0010] Therefore, exploring and designing new gas diffusion layer materials and improving the shortcomings of current gas diffusion layer materials in order to improve the electricity-hydrogen-electricity conversion efficiency and control cost growth are issues that need to be urgently addressed by technicians in this field. Summary of the invention
[0011] In view of the defects existing in the above-mentioned prior art, the present invention provides a titanium-based porous material for a gas diffusion layer and a preparation method thereof, wherein the titanium-based porous material comprises a titanium felt substrate and a microporous titanium layer attached to the titanium felt substrate; wherein the average pore size of the titanium felt substrate is 30-45 μm, and the porosity is 57%-76%; the microporous titanium layer comprises a first titanium layer and a second titanium layer; the first titanium layer is attached to the surface of the titanium felt substrate, the average pore size of the first titanium layer is 15-25 μm, and the porosity is 40%-65%; the second titanium layer is attached to the surface of the first titanium layer, the average pore size of the second titanium layer is 5-10 μm, and the porosity is 30-45%. The preparation method comprises spraying a first slurry onto the surface of the titanium felt substrate, removing the solvent and dispersant in the slurry by high-temperature calcination, the nano titanium powder in the first slurry is combined with the titanium felt substrate to form a raw material component of the first titanium layer, and then spraying a second slurry on the raw material component so that the micron titanium powder is combined with the first titanium layer, and finally obtaining a titanium-based porous material for a gas diffusion layer. The present invention prepares a gas diffusion layer with a gradient pore structure on a titanium felt substrate in a convenient and stable manner, thereby optimizing the interface relationship between the catalyst layer and the gas diffusion layer in a PEM fuel cell / PEM electrolyzer, reducing contact resistance, improving the utilization rate of low-loaded catalysts, inhibiting the deformation of the proton exchange membrane, and realizing efficient production and utilization of hydrogen energy.
[0012] In a first aspect, the present invention provides a titanium-based porous material for a gas diffusion layer, comprising:
[0013] A titanium felt substrate and a microporous titanium layer attached to the titanium felt substrate;
[0014] Among them, the average pore size of the titanium felt substrate is 30-45 μm, and the porosity is 57%-76%;
[0015] The microporous titanium layer includes a first titanium layer and a second titanium layer;
[0016] The first titanium layer is attached to the surface of the titanium felt substrate, the average pore size of the first titanium layer is 15-25 μm, and the porosity is 40%-65%;
[0017] The second titanium layer is attached to the surface of the first titanium layer, and the average pore diameter of the second titanium layer is 5-10 μm, and the porosity is 30-45%.
[0018] Furthermore, the average thickness of the titanium felt substrate is 250-500 μm, the average thickness of the first titanium layer is 45-90 μm, and the average thickness of the second titanium layer is 10-20 μm.
[0019] Furthermore, the average particle size of the first titanium layer particles is 20-30 μm, and the average particle size of the second titanium layer particles is 55-65 nm.
[0020] Furthermore, the current density of the titanium-based porous material used for the gas diffusion layer is not less than 2.1 A / cm2 , power density is not less than 1.4W / cm 2 , the shedding ratio is not more than 5%.
[0021] Furthermore, the average surface roughness of the microporous titanium layer is 5-15 μm.
[0022] Furthermore, the conductivity of the microporous titanium layer is (4×10 5 )-(12×10 5 )S·m -1 .
[0023] In a second aspect, the present invention further provides a method for preparing the titanium-based porous material for a gas diffusion layer as described above, which specifically comprises the following steps:
[0024] S1: coating a first slurry on a titanium felt substrate by ultrasonic spraying, and sintering at high temperature under an inert gas to prepare a raw material component;
[0025] S2: spraying the second slurry onto the raw material component obtained in S1, and sintering at high temperature under inert gas to obtain a titanium-based porous material for a gas diffusion layer.
[0026] Furthermore, the first slurry includes micron-grade titanium powder, isopropyl alcohol and Nafion solution, and the second slurry includes nano-grade titanium powder, isopropyl alcohol and PVB powder.
[0027] Furthermore, step S1 specifically includes the following steps:
[0028] S11: preparing a first slurry according to a solid content of 0.5-1.5 wt % by mixing micron-grade titanium powder, isopropanol, deionized water and Nafion solution, ultrasonically mixing and dispersing the mixture, and magnetically stirring the mixture to obtain a first slurry;
[0029] S12: applying the first slurry of S11 to the surface of the pretreated titanium felt substrate by ultrasonic spraying, the parameters of the ultrasonic spraying are as follows: the carrier gas is an inert gas, the nozzle height is 60-80 mm, the slurry discharge rate is 1-1.5 ml / min, the nozzle moving speed is 50-100 mm / s, and the bottom plate heating temperature is 80-150° C.;
[0030] S13: placing the titanium felt substrate coated with the first slurry obtained in S12 in a tubular furnace for high-temperature sintering to obtain a raw material component, wherein the parameters of the high-temperature sintering are as follows: an inert gas is introduced into the tubular furnace for protection, the flow rate of the inert gas is not less than 100 sccm, the temperature is 1100-1200°C, and the sintering time is not less than 4 hours.
[0031] Furthermore, the pretreatment of the titanium felt substrate surface specifically includes the following steps:
[0032] The titanium felt raw material is cut and flattened, and then ultrasonically cleaned in a mixed solution of propanol, deionized water and ethanol.
[0033] Furthermore, the content of the perfluorosulfonic acid polymer in the Nafion solution is 3-8 wt %.
[0034] Furthermore, step S2 specifically includes the following steps:
[0035] S21: preparing a second slurry according to a solid content of 0.5-1.5wt% by mixing nano-grade titanium powder, isopropyl alcohol, deionized water and PVB powder, ultrasonically mixing and dispersing the mixture uniformly, and magnetically stirring the mixture to obtain a second slurry, wherein the mass ratio of the nano-grade titanium powder to the PVB powder is (4-5):1;
[0036] S22: applying the second slurry of S21 to the raw material component obtained in S1 by ultrasonic spraying, the parameters of the ultrasonic spraying are as follows: the carrier gas is an inert gas, the nozzle height is 40-50 mm, the slurry discharge speed is 0.8-1 ml / min, the nozzle moving speed is 30-45 mm / s, and the bottom plate heating temperature is 80-150°C;
[0037] S23: placing the raw material component obtained in S22 in a tubular furnace, and calcining it at a high temperature in a nitrogen-protected atmosphere, wherein the calcination temperature is 500 to 700° C. and the calcination time is 1 to 3 hours, to obtain a titanium-based porous material for a gas diffusion layer.
[0038] The present invention provides a titanium-based porous material for a gas diffusion layer and a preparation method thereof, which has at least the following beneficial effects:
[0039] (1) The present invention prepares a gas diffusion layer with a gradient pore structure on a titanium felt substrate in a convenient and stable manner, thereby optimizing the interface relationship between the catalyst layer and the gas diffusion layer in a PEM fuel cell / PEM electrolyzer, reducing contact resistance, improving the utilization rate of low-loaded catalysts, inhibiting the deformation of the proton exchange membrane, and achieving efficient production and utilization of hydrogen energy.
[0040] (2) The first slurry prepared from micron-sized titanium powder is coated on the surface of the titanium felt substrate by ultrasonic spraying to form a first titanium layer with uniform pore size and porosity. The first titanium layer has a high porosity and a large thickness, and will not produce mass transfer resistance to the gas diffusion layer. In addition, the large micron-sized titanium powder particles will not scatter into the pores of the titanium felt substrate, resulting in blockage and destruction of the original pore structure of the titanium felt substrate.
[0041] (3) A second titanium layer is attached to the surface of the first titanium layer. The particle size, porosity and thickness of the second titanium layer are smaller than those of the first titanium layer, which can ensure the electron transmission efficiency of the gas diffusion layer structure and retain the moisture in the adjacent anode / cathode catalyst layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a cross-sectional microscopic TEM image of a titanium-based porous material for a gas diffusion layer provided by the present invention.
[0043] Description of reference numerals:
[0044] 10-titanium felt substrate, 20-microporous titanium layer, 21-first titanium layer, 22-second titanium layer. DETAILED DESCRIPTION
[0045] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.
[0047] It should also be noted that the term "includes", "comprising" or any other variation thereof is intended to cover non-exclusive inclusion, so that a commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprising a ..." do not exclude the existence of other identical elements in the commodity or device including the elements.
[0048] Traditional gas diffusion layer structures, such as titanium felt, titanium mesh or titanium foam, as well as modified treatments of traditional gas diffusion layer structures, still have the disadvantage of uniform fiber / foam pore morphology on their surfaces. This pore size and distribution state still cannot meet the requirements for precise control of liquid / gas / electron / heat distribution in the gas diffusion layer.
[0049] In addition, the pore structure and filamentous fibers of the existing gas diffusion layer will increase its surface roughness and reduce the interfacial contact area with the anode / cathode catalyst layer, which will not only reduce the catalyst utilization rate, but also cause uneven pressure distribution during compression and damage the proton exchange membrane.
[0050] Based on the above drawbacks, it is necessary to explore and design a structure with sufficient pores on the surface of the gas diffusion layer to allow reactants and products to pass through, and to conduct electricity and heat in both the plane and vertical directions. Especially for the side in contact with the anode / cathode catalyst layer, the pores cannot be too large and must have a certain degree of flexibility. In addition, the gas diffusion layer as a whole must also maintain sufficient rigidity to support the proton exchange membrane.
[0051] like Figure 1 As shown, the present invention provides a titanium-based porous material for a gas diffusion layer, comprising:
[0052] A titanium felt substrate 10 and a microporous titanium layer 20 attached to the titanium felt substrate 10;
[0053] The average pore size of the titanium felt substrate 10 is 30-45 μm, and the porosity is 57%-76%;
[0054] The microporous titanium layer 20 includes a first titanium layer 21 and a second titanium layer 22;
[0055] The first titanium layer 21 is attached to the surface of the titanium felt substrate 10, and the average pore size of the first titanium layer 21 is 15-25 μm, and the porosity is 40%-65%;
[0056] The second titanium layer 22 is attached to the surface of the first titanium layer 21 . The average pore size of the second titanium layer 22 is 5-10 μm, and the porosity is 30-45%.
[0057] Preferably, the average thickness of the titanium felt substrate 10 is 250-500 μm, the average thickness of the first titanium layer 21 is 45-90 μm, and the average thickness of the second titanium layer 22 is 10-20 μm.
[0058] Preferably, the average particle size of the particles in the first titanium layer 21 is 20-30 μm, and the average particle size of the particles in the second titanium layer 22 is 55-65 nm.
[0059] Preferably, the current density of the titanium-based porous material used for the gas diffusion layer is not less than 2.1 A / cm 2 , power density is not less than 1.4W / cm 2 , the shedding ratio is not more than 5%.
[0060] Preferably, the average surface roughness of the microporous titanium layer 20 is 5-15 μm.
[0061] Preferably, the conductivity of the microporous titanium layer 20 is (4×10 5 )-(12×10 5 )S·m -1 .
[0062] The titanium-based porous material for the gas diffusion layer provided by the present invention has a gradient pore structure. Based on the mass transfer and heat transfer characteristics of the titanium felt substrate, with the aid of an attached double-layer microporous titanium layer, the contact area with the anode / cathode catalyst layer is larger and the pressure distribution is more uniform, thereby improving the utilization rate of the catalyst while reducing the risk of damage to the proton exchange membrane.
[0063] In addition, the present invention also provides a method for preparing the titanium-based porous material for a gas diffusion layer as described above, which specifically comprises the following steps:
[0064] S1: coating a first slurry on a titanium felt substrate by ultrasonic spraying, and sintering at high temperature under an inert gas to prepare a raw material component;
[0065] S2: spraying the second slurry onto the raw material component obtained in S1, and sintering at high temperature under inert gas to obtain a titanium-based porous material for a gas diffusion layer.
[0066] Furthermore, the first slurry includes micron-grade titanium powder, isopropyl alcohol and Nafion solution, and the second slurry includes nano-grade titanium powder, isopropyl alcohol and PVB powder.
[0067] Furthermore, step S1 specifically includes the following steps:
[0068] S11: preparing a first slurry according to a solid content of 0.5-1.5 wt % by mixing micron-grade titanium powder, isopropanol, deionized water and Nafion solution, ultrasonically mixing and dispersing the mixture, and magnetically stirring the mixture to obtain a first slurry;
[0069] S12: applying the first slurry of S11 to the surface of the pretreated titanium felt substrate by ultrasonic spraying, the parameters of the ultrasonic spraying are as follows: the carrier gas is an inert gas, the nozzle height is 60-80 mm, the slurry discharge rate is 1-1.5 ml / min, the nozzle moving speed is 50-100 mm / s, and the bottom plate heating temperature is 80-150° C.;
[0070] S13: placing the titanium felt substrate coated with the first slurry obtained in S12 in a tubular furnace for high-temperature sintering to obtain a raw material component, wherein the parameters of the high-temperature sintering are as follows: an inert gas is introduced into the tubular furnace for protection, the flow rate of the inert gas is not less than 100 sccm, the temperature is 1100-1200°C, and the sintering time is not less than 4 hours.
[0071] Furthermore, the pretreatment of the titanium felt substrate surface specifically includes the following steps:
[0072] The titanium felt raw material is cut and flattened, and then ultrasonically cleaned in a mixed solution of propanol, deionized water and ethanol.
[0073] Furthermore, the content of the perfluorosulfonic acid polymer in the Nafion solution is 3-8 wt %.
[0074] Furthermore, step S2 specifically includes the following steps:
[0075] S21: preparing a second slurry according to a solid content of 0.5-1.5wt% by mixing nano-grade titanium powder, isopropyl alcohol, deionized water and PVB powder, ultrasonically mixing and dispersing the mixture uniformly, and magnetically stirring the mixture to obtain a second slurry, wherein the mass ratio of the nano-grade titanium powder to the PVB powder is (4-5):1;
[0076] S22: applying the second slurry of S21 to the raw material component obtained in S1 by ultrasonic spraying, the parameters of the ultrasonic spraying are as follows: the carrier gas is an inert gas, the nozzle height is 40-50 mm, the slurry discharge speed is 0.8-1 ml / min, the nozzle moving speed is 30-45 mm / s, and the bottom plate heating temperature is 80-150°C;
[0077] S23: placing the raw material component obtained in S22 in a tubular furnace, and calcining it at a high temperature in a nitrogen-protected atmosphere, wherein the calcination temperature is 500 to 700° C. and the calcination time is 1 to 3 hours, to obtain a titanium-based porous material for a gas diffusion layer.
[0078] Embodiment 1:
[0079] Example 1 A titanium-based porous material for a gas diffusion layer was prepared.
[0080] In Example 1, the specific preparation process is as follows:
[0081] S1: coating a first slurry on a titanium felt substrate by ultrasonic spraying, and then sintering at a high temperature under an inert gas to prepare a raw material component, wherein the first slurry includes micron-grade titanium powder, isopropanol and Nafion solution;
[0082] Prepare the first slurry according to the solid content of 1wt%: weigh 0.48g of titanium powder with an average particle size of 20μm and add it to a wire-mouth reagent bottle, use a pipette to measure 66.22ml of isopropanol and add it to the wire-mouth reagent bottle, use a pipette to measure 5.4ml of deionized water and add it to the wire-mouth reagent bottle, use a pipette to measure 2.53ml of 5% mass fraction Nafion solution and add it to the wire-mouth reagent bottle;
[0083] After the lid is tightly closed, the mixture is placed in a large beaker filled with ice water for an ice water bath, and the beaker is placed in an ultrasonic cleaning machine, and ultrasonically mixed for 15 minutes at a power of 80% to evenly mix the slurry; the reagent bottle after ultrasonic mixing is kept in an ice water bath and placed in an ultrasonic cell disruptor, and ultrasonically dispersed for 20 minutes at a power of 40% to evenly disperse the slurry; a magnet is added to the dispersed slurry, and the lid is tightly closed and stirred on a magnetic stirrer at a speed of 600 rpm for 24 hours to obtain a first slurry;
[0084] A commercial titanium felt with a thickness of 0.25 mm, a porosity of 56%, and an average pore size of 30 μm was selected as the base material, and was cut into a square of 3.5 cm×3.5 cm. The titanium felt raw material was cut and flattened, and ultrasonically cleaned in a mixed solution of propanol, deionized water, and ethanol to obtain a pretreated titanium felt base;
[0085] A stainless steel cover plate with a 2.7 cm × 2.7 cm square opening in the middle was used to cover the 3.5 cm × 3.5 cm titanium felt obtained in S13, and the first slurry was applied to the surface of the pretreated titanium felt substrate by ultrasonic spraying. The parameters of the ultrasonic spraying were as follows: the carrier gas was an inert gas, the nozzle height was 80 mm, the slurry discharge rate was 1 ml / min, the nozzle moving speed was 60 mm / s, and the bottom plate heating temperature was 105°C;
[0086] The titanium felt substrate coated with the first slurry is placed in a tubular furnace for high-temperature sintering to obtain a raw material component, wherein the parameters of the high-temperature sintering are as follows: inert gas protection is introduced into the tubular furnace, the flow rate of the inert gas is 100 sccm, the temperature is 1100°C, and the sintering time is 4 hours.
[0087] S2: spraying the second slurry onto the raw material component obtained in S1, and then sintering at high temperature under an inert gas to obtain a titanium-based porous material for a gas diffusion layer; wherein the second slurry includes nano-grade titanium powder, isopropyl alcohol and PVB powder;
[0088] Prepare the second slurry according to the solid content of 1wt%: weigh 0.12g PVB powder with a balance and add it to a wire mouth reagent bottle, use a pipette to measure 68.75ml of isopropanol and add it to the wire mouth reagent bottle, cover the lid and put it into a large beaker filled with ice water in an ice water bath, put the beaker into an ultrasonic cleaner, and mix it evenly with 80% power for 10 minutes; weigh 0.48g of 60nm titanium powder with a balance and add it to the wire mouth reagent bottle, use a pipette to measure 5.4ml of deionized water and add it to the wire mouth reagent bottle;
[0089] After the lid is tightly closed, the mixture is placed in a large beaker filled with ice water for an ice water bath. The beaker is placed in an ultrasonic cleaning machine and ultrasonically dispersed at 80% power for 15 minutes to evenly mix the slurry. The reagent bottle after ultrasonic mixing is kept in an ice water bath and placed in an ultrasonic cell disruptor for 20 minutes at 40% power to evenly disperse the slurry. A magnet is added to the dispersed slurry, the lid is tightly closed, and the mixture is stirred at 700 rpm for 24 hours on a magnetic stirrer to obtain an evenly mixed second slurry.
[0090] The second slurry is applied to the raw material component obtained in S1 by ultrasonic spraying. The parameters of ultrasonic spraying are as follows: the carrier gas is an inert gas, the nozzle height is 50 mm, the slurry discharge rate is 0.8 ml / min, the nozzle moving speed is 45 mm / s, and the bottom plate heating temperature is 105°C;
[0091] The obtained raw material parts were placed in a tubular furnace and calcined at high temperature in a nitrogen-protected atmosphere at a temperature of 500° C. for 3 hours to obtain a titanium-based porous material for a gas diffusion layer.
[0092] The titanium-based porous material for the gas diffusion layer prepared in this embodiment includes: a titanium felt substrate and a microporous titanium layer attached to the titanium felt substrate; the microporous titanium layer includes a first titanium layer and a second titanium layer; the first titanium layer is attached to the surface of the titanium felt substrate, the average pore size of the first titanium layer is about 20 μm, and the porosity is about 60%; the second titanium layer is attached to the surface of the first titanium layer, the average pore size of the second titanium layer is about 8 μm, and the porosity is about 40%. The average thickness of the first titanium layer is about 60 μm, and the average thickness of the second titanium layer is about 15 μm.
[0093] The current density of the titanium-based porous material for the gas diffusion layer prepared in this embodiment is 2.26 A / cm 2 (@1.8V), power density is 1.55W / cm 2 (@0.6V), the shedding ratio is 3.75%.
[0094] Embodiment 2:
[0095] Example 2: A titanium-based porous material for a gas diffusion layer is prepared.
[0096] In Example 2, relative to the preparation process of Example 1, the following parameters were adjusted:
[0097] In step S12, the amount of the first slurry is increased so that the average thickness of the first titanium layer in the prepared titanium-based porous material for a gas diffusion layer is about 80 μm.
[0098] The current density of the titanium-based porous material for the gas diffusion layer prepared in this embodiment is 2.15 A / cm2 (@1.8V), power density is 1.45W / cm 2 (@0.6V), the shedding ratio is 4.67%.
[0099] Embodiment 3:
[0100] Example 3: A titanium-based porous material for a gas diffusion layer is prepared.
[0101] In Example 3, relative to the preparation process of Example 1, the following parameters were adjusted:
[0102] In step S13, the high temperature calcination temperature is 1200°C and the sintering time is 4 hours.
[0103] The current density of the titanium-based porous material for the gas diffusion layer prepared in this embodiment is 2.18 A / cm 2 (@1.8V), power density is 1.49W / cm 2 (@0.6V), the shedding ratio is 2.19%.
[0104] Embodiment 4:
[0105] Example 4: A titanium-based porous material for a gas diffusion layer is prepared.
[0106] In Example 4, relative to the preparation process of Example 1, the following parameters were adjusted:
[0107] In step S23, the sintering temperature of high temperature calcination is 700°C and the sintering time is 2 hours.
[0108] The current density of the titanium-based porous material for the gas diffusion layer prepared in this embodiment is 2.13 A / cm 2 (@1.8V), power density is 1.43W / cm 2 (@0.6V), the shedding ratio is 4.87%.
[0109] Comparative Example 1:
[0110] Comparative Example 1: A titanium-based porous material for a gas diffusion layer was prepared.
[0111] In Comparative Example 1, relative to the preparation process of Example 1, the following parameters were adjusted:
[0112] In this comparative example, step S2 is omitted, and the raw material component prepared in step S1 is directly used as the titanium-based porous material for the gas diffusion layer.
[0113] The current density of the titanium-based porous material for the gas diffusion layer prepared in this comparative example is 2.02 A / cm 2 (@1.8V), power density is 1.33W / cm 2 (@0.6V), the shedding ratio is 3.15%.
[0114] Comparative Example 2:
[0115] Comparative Example 2: A titanium-based porous material for a gas diffusion layer was prepared.
[0116] In Comparative Example 2, relative to the preparation process of Example 1, the following parameters were adjusted:
[0117] In this comparative example, the second slurry is directly used in step S1, the second slurry is coated on the titanium felt substrate, and the titanium-based porous material for the gas diffusion layer is prepared by high-temperature sintering under an inert gas.
[0118] The components and the uniform mixing process of the second slurry are consistent with those of Example 1. The ultrasonic spraying parameters of the second slurry and the high-temperature sintering parameters after spraying are also consistent with those of Example 1.
[0119] The current density of the titanium-based porous material for the gas diffusion layer prepared in this comparative example is 1.89 A / cm 2 (@1.8V), power density is 1.30W / cm 2 (@0.6V), the shedding ratio is 9.98%.
[0120] Comparative Example 3:
[0121] Comparative Example 3: Prepare a titanium-based porous material for a gas diffusion layer.
[0122] In Comparative Example 3, relative to the preparation process of Example 1, the following parameters were adjusted:
[0123] In step S21, the second slurry includes nano-sized titanium powder, isopropyl alcohol and Nafion solution. In this comparative example, the solid content of the nano-sized titanium powder is 1 wt %, and the mixing process of the second slurry is the same as that of the first slurry.
[0124] In step S22, the ultrasonic spraying process of the second slurry is consistent with the process of Example 1.
[0125] The current density of the titanium-based porous material for the gas diffusion layer prepared in this comparative example is 2.09 A / cm 2 (@1.8V), power density is 1.37W / cm 2 (@0.6V), the shedding ratio is 26.85%.
[0126] Comparative Example 4
[0127] Comparative Example 4: A titanium-based porous material for a gas diffusion layer was prepared.
[0128] In Comparative Example 4, relative to the preparation process of Example 1, the following parameters are adjusted: in step S11, the first slurry includes micron-sized titanium powder, isopropyl alcohol and Nafion solution, wherein the average particle size of the micron-sized titanium powder is 45 μm.
[0129] The current density of the titanium-based porous material for the gas diffusion layer prepared in this comparative example is 1.98 A / cm 2 (@1.8V), power density is 1.31W / cm 2 (@0.6V), the shedding ratio is 6.13%.
[0130] Comparative Example 5:
[0131] Comparative Example 5: A titanium-based porous material for a gas diffusion layer was prepared.
[0132] In Comparative Example 5, relative to the preparation process of Example 1, the following parameters are adjusted: in step S22, the amount of the second slurry is increased so that the average thickness of the second titanium layer in the prepared titanium-based porous material for a gas diffusion layer is about 30 μm.
[0133] The current density of the titanium-based porous material for the gas diffusion layer prepared in this comparative example is 1.91 A / cm 2 (@1.8V), power density is 1.32W / cm 2 (@0.6V), the shedding ratio is 3.35%.
[0134] Comparative Example 6:
[0135] Comparative Example 6: Prepare a titanium-based porous material for a gas diffusion layer.
[0136] In Comparative Example 6, relative to the preparation process of Example 1, the following parameters were adjusted:
[0137] In step S13, the high temperature sintering temperature is 700° C. and the sintering time is 3 hours.
[0138] The current density of the titanium-based porous material for the gas diffusion layer prepared in this comparative example is 1.93 A / cm 2 (@1.8V), power density is 1.28W / cm 2 (@0.6V), the shedding ratio is 37.59%.
[0139] Comparative Example 7:
[0140] Comparative Example 7: Prepare a titanium-based porous material for a gas diffusion layer.
[0141] In Comparative Example 7, relative to the preparation process of Example 1, the following parameters were adjusted:
[0142] In step S23, the high temperature sintering temperature is 1100° C. and the sintering time is 4 hours.
[0143] The current density of the titanium-based porous material for the gas diffusion layer prepared in this comparative example is 1.92 A / cm 2 (@1.8V), power density is 1.32W / cm 2 (@0.6V), the shedding ratio is 5.17%.
[0144] Testing process:
[0145] The gas diffusion layers obtained in Examples 1-4 and Comparative Examples 1-7 were used as anode gas diffusion layers of PEM electrolyzers to carry out IV (current density-voltage) curve tests for electrochemical characterization of the electrolyzers, as cathode gas diffusion layers of PEM fuel cells to carry out volt-ampere characteristic curve measurements for electrochemical characterization of fuel cells, and experimental tests on the bonding state of the microporous titanium layer were carried out.
[0146] The test conditions of the PEM electrolyzer are as follows: the operating temperature of the PEM electrolyzer is 80°C, the pressure is normal pressure, the electrolyte used is 30% mass fraction KOH solution, and the diaphragm used is Toray's third-generation PPS diaphragm. Accordingly, the voltage change response signal is collected, and the IV (current density-voltage) curve diagram is tested respectively to obtain the current density when the voltage is 1.8V.
[0147] The PEM fuel cell test conditions are as follows: the operating temperature of the PEM fuel cell is 80°C, the gas back pressure on both sides of the fuel cell is 0.2MPa, and fully humidified hydrogen and oxygen are input at a flow rate of 500mL / min. Accordingly, the voltage change response signal is collected, and the IV (current-voltage) curve and power density curve are tested respectively.
[0148] The test conditions for the bonding state of the microporous titanium layer are as follows: the sample size is 2.5cm×2.5cm, weighed, and then placed in a beaker containing 50ml of anhydrous ethanol and 50ml of ultrapure water, and the beaker is placed in an ultrasonic cleaning machine with a power of 100W, and the ultrasonic operation is performed for 15 minutes. After the operation, each sample is taken out, dried and weighed, and the weight difference before and after the ultrasonic operation is calculated. The ratio of the weight difference to the original weight is used as the shedding ratio (%), and the shedding ratio is used to measure the bonding state of the microporous titanium layer of the sample.
[0149] Table 1 Test data table of embodiments and comparative examples
[0150]
[0151]
[0152] From the test results in Table 1, we can see that:
[0153] For the most important parameters of the gas diffusion layer, current density and power density, the titanium-based porous materials of Examples 1-4 were used as gas diffusion layers, and the current density at a voltage of 1.8 V was higher than 2.1 A / cm 2 The power density at a response voltage of 0.6 V is higher than 1.4 W / cm 2 .
[0154] In addition, the shedding ratio is tested from the service performance analysis of the titanium-based porous material and the bonding state index of the microporous titanium layer. The shedding ratios of the titanium-based porous materials given in Examples 1-4 are all less than 5%.
[0155] The current density performance of the gas diffusion layer can be summarized by the IV curve. The current is usually normalized by the effective area to obtain the current density (unit A / cm 2 ), when maintaining a constant voltage determined by thermodynamics, how much current density will be output. In the actual application of the electrolyzer, the voltage is constant, the more current is output, the greater the total power released.
[0156] Similarly, the titanium-based materials given in Comparative Examples 1-7 as gas diffusion layers have a current density of less than 2.1 A / cm at a voltage of 1.8 V. 2 .
[0157] The power density performance of the gas diffusion layer can be obtained from the power density curve of the PEM fuel cell test, that is, at a response voltage of 0.6V, the current fluctuation signal is collected. The greater the power density, the better the performance of the PEM fuel cell assembled with the gas diffusion layer.
[0158] The titanium-based materials given in Comparative Examples 1-7 are used as gas diffusion layers. At a response voltage of 0.6 V, the power density is lower than 1.4 W / cm 2 .
[0159] It can be concluded from the above test results that the titanium-based materials given in Comparative Examples 1-7 cannot take into account both mass transfer and electron transfer, which affects the electrolysis efficiency.
[0160] Although preferred embodiments of the present invention have been described, additional changes and modifications may be made to these embodiments by those skilled in the art once the basic inventive concepts are known. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a titanium-based porous material for a gas diffusion layer, characterized in that: The titanium-based porous material comprises: a titanium felt substrate and a microporous titanium layer attached to the titanium felt substrate; Among them, the average pore size of the titanium felt substrate is 30-45 μm, and the porosity is 57%-76%; The microporous titanium layer includes a first titanium layer and a second titanium layer; The first titanium layer is attached to the surface of the titanium felt substrate, the first titanium layer has an average pore size of 15-25 μm, a porosity of 40%-65%, and an average particle size of particles for preparing the first titanium layer of 20-30 μm; The second titanium layer is attached to the surface of the first titanium layer, the second titanium layer has an average pore size of 5-10 μm, a porosity of 30%-45%, and an average particle size of particles for preparing the second titanium layer of 55-65 nm; The method specifically comprises the following steps: S1: coating a first slurry on a titanium felt substrate by ultrasonic spraying, and sintering at high temperature under inert gas to prepare a raw material component, wherein the first slurry includes micron-grade titanium powder, isopropanol and Nafion solution, and the parameters of high-temperature sintering are as follows: an inert gas protection is introduced into a tubular furnace, the flow rate of the inert gas is not less than 100 sccm, the temperature is 1100-1200 °C, and the sintering time is not less than 4 hours; S2: spraying the second slurry onto the raw material component obtained in S1, and calcining at high temperature under inert gas to obtain a titanium-based porous material for a gas diffusion layer, wherein the second slurry includes nano-grade titanium powder, isopropyl alcohol and PVB powder, the calcination temperature is 500-700°C, and the calcination time is 1-3h.
2. The method for preparing a titanium-based porous material for a gas diffusion layer according to claim 1, characterized in that: The average thickness of the first titanium layer is 45-90 μm, and the average thickness of the second titanium layer is 10-20 μm.
3. The method for preparing a titanium-based porous material for a gas diffusion layer according to claim 1 or 2, characterized in that: The current density of titanium-based porous materials used for gas diffusion layers is not less than 2.1 A / cm 2 , power density not less than 1.4 W / cm 2 , the shedding ratio is not more than 5%.
4. The method for preparing a titanium-based porous material for a gas diffusion layer according to claim 1, characterized in that: Step S1 specifically includes the following steps: S11: preparing a first slurry according to a solid content of 0.5-1.5 wt% by mixing micron-sized titanium powder, isopropanol, deionized water and Nafion solution, ultrasonically mixing and dispersing the mixture uniformly, and magnetically stirring the mixture to obtain a first slurry; S12: applying the first slurry of S11 to the surface of the pretreated titanium felt substrate by ultrasonic spraying, the parameters of the ultrasonic spraying are as follows: the carrier gas is an inert gas, the nozzle height is 60-80 mm, the slurry discharge rate is 1-1.5 ml / min, the nozzle moving speed is 50-100 mm / s, and the bottom plate heating temperature is 80-150 °C; S13: placing the titanium felt substrate coated with the first slurry obtained in S12 in a tubular furnace for high-temperature sintering to obtain a raw material component.
5. The method for preparing a titanium-based porous material for a gas diffusion layer according to claim 4, characterized in that: The pretreatment of the titanium felt substrate surface specifically includes the following steps: The titanium felt raw material is cut and flattened, and then ultrasonically cleaned in a mixed solution of propanol, deionized water and ethanol.
6. The method for preparing a titanium-based porous material for a gas diffusion layer according to claim 4, characterized in that: The content of perfluorosulfonic acid polymer in Nafion solution is 3-8 wt%.
7. The method for preparing a titanium-based porous material for a gas diffusion layer according to claim 1, characterized in that: Step S2 specifically includes the following steps: S21: preparing a second slurry according to a solid content of 0.5-1.5 wt% by mixing nano-sized titanium powder, isopropyl alcohol, deionized water and PVB powder, ultrasonically mixing and dispersing the mixture, and magnetically stirring the mixture to obtain a second slurry, wherein the mass ratio of the nano-sized titanium powder to the PVB powder is (4-5):1; S22: applying the second slurry of S21 to the raw material component obtained in S1 by ultrasonic spraying, the parameters of the ultrasonic spraying are as follows: the carrier gas is an inert gas, the nozzle height is 40-50 mm, the slurry discharge speed is 0.8-1 ml / min, the nozzle moving speed is 30-45 mm / s, and the bottom plate heating temperature is 80-150 °C; S23: placing the raw material component obtained in S22 in a tubular furnace, and calcining it at a high temperature under a nitrogen-protected atmosphere to obtain a titanium-based porous material for a gas diffusion layer.
Citation Information
Patent Citations
Porous metal gas diffusion layer, solid polymer fuel cell having the same, and water electrolyzer
JP2022145670A
Gradient porous metal felt for water electrolyser and preparation method
CN115646071A
Gas diffusion layer and preparation method therefor
WO2022126935A1